ChemInform Abstract: Nucleophilic β‐Alkenylation of N‐Alkoxyenamines: An Umpolung Strategy for the Preparation of β, γ‐Unsaturated Ketones. Issue 37 (August 2016) - Nandi, Raj Kumar; Takeda, Norihiko; Ueda, Masafumi; Miyata, Okiko
Abstract: A procedure for nucleophilic β‐alkenylation of N‐alkoxyenamines with alkenyl aluminum reagents under mild conditions is reported.